Exploring Biological Interactions: A New Pyrazoline as a Versatile Fluorescent Probe for Energy Transfer and Cell Staining Applications - Dr. Burcu Meryem Beşer; Berat Yildirim (ChemistryOpen, 2023)
Abstract Fluorescent dyes are used in biological systems, because they are highly sensitive and selective. In this work, we investigated the fluorescent probe properties of 2‐(5‐(pyridin‐2‐yl)‐1H‐pyrazol‐3‐yl) phenol (PYDP) in two media [sodium dodecyl sulfate (SDS) and human serum albumin (HSA)]. Energy transfer parameters, photophysical and thermodynamic parameters of probe were determined. We investigated cytotoxicity of PYDP against colorectal adenocarcinoma cell lines (HT‐29), breast cancer cell lines (MCF‐7) and 3T3‐L1 adipocytes (3T3 L1) cells. The cell staining property of PYDP was monitored using a confocal microscope. The results showed that PYDP binds to HSA, bindings are due to electrostatic/ionic interactions, and the binding process is spontaneous. PYDP was found to exhibit negligible cytotoxicity at high concentrations, and confocal microscope images showed that PYDP stained the cytoplasm of MCF‐7 cells.